2013
DOI: 10.4240/wjgs.v5.i4.123
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of intersphincteric fistula tract and its modification: Results from treatment of complex fistula

Abstract: There was no difference in results between LIFT and LIFT plus operations. The LIFT procedure is a good option for maintaining continence in management of fistula-in-ano.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 42 publications
1
50
0
7
Order By: Relevance
“…9 This principle has been adopted by some practitioners of LIFT in a modification that involves laying open the intersphincteric portion of the tract but suturing close the remnant tract that traverses the external sphincter. 21 In the series of 93 patients reported by Tan et al, the median healing time was 4 weeks (range: 1-12 weeks). Hence, for patients with a persistent fistula opening or draining intersphincteric wound, we recommend waiting up to 3 months before declaring the procedure a failure.…”
Section: Management Of Failuresmentioning
confidence: 95%
See 1 more Smart Citation
“…9 This principle has been adopted by some practitioners of LIFT in a modification that involves laying open the intersphincteric portion of the tract but suturing close the remnant tract that traverses the external sphincter. 21 In the series of 93 patients reported by Tan et al, the median healing time was 4 weeks (range: 1-12 weeks). Hence, for patients with a persistent fistula opening or draining intersphincteric wound, we recommend waiting up to 3 months before declaring the procedure a failure.…”
Section: Management Of Failuresmentioning
confidence: 95%
“…9 Other consistent risk factors across several studies include obesity and smoking. 12,16,21 The contribution of a prior history of surgery has been less clear. Liu et al and Abcarian et al found it to be a significant risk factor.…”
Section: Risk Factors For Failuresmentioning
confidence: 97%
“…16 The impairment of continence has a worse effect on quality of life and is more distressing for patients than the presence of the fistula itself, so the sphincter saving techniques are more popular. Examples of sphincter saving methods include fibrin glue injection, anal fistula plug, endorectal advancement flap (ERAF) and ligation of intersphincteric fistula tract (LIFT).…”
Section: Postoperative Follow Up and Complicationsmentioning
confidence: 99%
“…[5][6][7] All patients were informed about the procedures including using BRCC, and the written consent meeting the standards set by the hospitals' institutional review board was obtained before MRI examination. [5][6][7] All patients were informed about the procedures including using BRCC, and the written consent meeting the standards set by the hospitals' institutional review board was obtained before MRI examination.…”
Section: Patient Selection and Data Collectionmentioning
confidence: 99%
“…2 The classification of anal fistula was proposed by Parks et al, who assigned the fistulas into 1 of 4 groups: intersphincteric, transsphincteric, suprasphincteric, and extrasphincteric. 2,[5][6][7] For the patients with chronic inflammatory disease of the gastrointestinal tract such as Crohn disease or with the repeated surgical treatments, 2 or more fistulas or internal openings, sometimes the iatrogenic internal openings caused by operations, may be detected, and the location of these lesions may be very deep. 2,[5][6][7] For the patients with chronic inflammatory disease of the gastrointestinal tract such as Crohn disease or with the repeated surgical treatments, 2 or more fistulas or internal openings, sometimes the iatrogenic internal openings caused by operations, may be detected, and the location of these lesions may be very deep.…”
mentioning
confidence: 99%